Theological interpretation and Isaiah 53 : a critical comparison of Bernhard Duhm, Brevard Childs, and Alec Motyer /: a critical comparison of Bernhard Duhm, Brevard Childs, and Alec Motyer. (2014) - Dr, Shepherd, Charles E
No abstract available